Hydrothermal growth of TiO2 nanorod arrays and in situ conversion to nanotube arrays for highly efficient quantum dot-sensitized solar cells - Lim, Chiew Keat (2014)
TiO2 nanorod (NR) and nanotube (NT) arrays grown on transparent conductive substrates are attractive electrode for solar cells. In this paper, TiO2 NR arrays are hydrothermally grown on FTO substrate, and are in situ converted into NT arrays by hydrothermally etching. The TiO2 NR arrays are reported as single crystalline, but the TiO2 NR arrays are demonstrated to be polycrystalline with a bundle of 2–5 nm single crystalline nanocolumns grown along [001] throughout the whole NR from bottom to top. TiO2 NRs can be converted to NTs by hydrothermal selective etching of the (001) core and remaining the inert sidewall of (110) face. A growth mechanism of the NR and NT arrays is proposed. Quantum dot-sensitized solar cells (QDSCs) are fabricated by coating CdSe QDs on to the TiO2 arrays. After conversion from NRs to NTs, more QDs can be filled in the NTs and the energy conversion efficiency of the QDSCs almost double.